Microsurgical autologous breast reconstruction in the midst of a pandemic: A single-unit COVID-19 experience. Issue 1 (January 2022) - Ho, Weiguang; Köhler, Guido; Haywood, Richard M; Rosich-Medina, Anais; Masud, Dhalia
Summary: Introduction: COVID-19 has disrupted the provision of breast reconstructive services throughout the UK. Autologous free flap breast reconstruction was restarted in our unit on 3 June 2020. We aimed to compare the unit's performance of microsurgical autologous breast reconstruction in the "post-COVID" period compared with the exact time period in the preceding year. Methods: We retrospectively reviewed prospectively collected data in the "pre-COVID" (from 3 June 2019 to 31 December 2019) and "post-COVID" period (from 3 June 2020 to 31 December 2020). Patient demographics included age, body mass index, co-morbidities, Anaesthesiologists (ASA) grade and smoking status. Surgical factors included neoadjuvant chemotherapy, previous chest wall radiotherapy, unilateral or bilateral reconstruction, reconstruction timing, number of pedicles, contralateral symmetrisation and other procedures. dependant variables were ischaemic time, operative time, mastectomy weight, flap weight, length of stay, return to theatre and complication rates. The number of trainers and trainees present in theatre was recorded and analysed. Results: Fewer DIEP flaps were performed in the "post-COVID" period (45 vs. 29). No significant difference was observed in mastectomy resection weight, but flap weight was significantly increased. No significant difference was found in ischaemic time as well. The postoperative length of stay was significantly reduced. No significant difference was found in rates of return to theatre, unplanned admission, infection, haematoma, seroma or wound dehiscence. No cases of venous thromboembolism or flap failures were recorded. The mean number of trainers and trainees, and the trainee-to-trainer ratio was not found to be significantly different between cohorts. Conclusion: Although fewer cases were performed, autologous breast reconstruction was safely delivered throughout the COVID-19 pandemic in the first wave without affecting training.